The relationship of irisin, apelin-13, and immunological markers il-1α & amp, il-1β with diabetes in kidney failure patients: Irisin, apelin-13, and inflammatory markers in diabetic kidney failure - A. Sakran, Nawar; Cherif, Slim; Shawqi Algburi, Firas (Cellular and Molecular Biology, 2025)
Chronic kidney disease (CKD) is often complicated by diabetes, impacting various biochemical and immunological markers. This study aimed to investigate the relationship between irisin, apelin-13, and immunological markers IL-1α and IL-1β in diabetic patients with CKD. This cross-sectional study was conducted from January to June 2023 in a tertiary care hospital in Tikrit City, Iraq. This study included 120 CKD patients and a control group including 20 healthy individuals. Patients were included in the study by convenience sampling method. Participants were evaluated using ELISA kits for irisin, apelin-13, and cytokines, with blood samples analyzed for relevant biochemical markers. Patients had irisin levels of 10.98 ± 2.5 ng/mL, significantly different from non-diabetic patients (12.40 ± 3.54 ng/mL) and controls (5.36 ± 1.06 ng/mL) (p<0.001). Apelin-13 was higher in diabetic patients (537.71 ± 124.78 pg/mL) compared to controls (181.26 ± 29.98 pg/mL) (p<0.001). IL-1α levels in diabetic patients were 715.30 ± 392.48 pg/mL, significantly higher than in control patients (206.27 ± 26.49 pg/mL) (p<0.001). IL-1β levels were 351.50 ± 81.82 pg/mL in diabetics, also higher than in control (145.79 ± 38.49 pg/mL) (p<0.001). The study highlights significant associations between biochemical markers and CKD in diabetic patients. Elevated levels of irisin, apelin-13, IL-1α, and IL-1β may serve as potential biomarkers for diabetes-related CKD complications.